THE CONCEPT OF AUTHORIZATION (BEZIT) IN SALES AND PURCHASE TRANSACTIONS OF VIRTUAL PROPERTY - Yudhantaka, Lintang; Nugraheni, Ninis (Faculty of Law, Universitas Sebelas Maret, 2019)
Virtual property such as softwares, e-books, and games are commonly seen as things with economic values. This study discusses the position of bezitter in the authorization of virtual property and the object delivery in sales and purchase transactions of virtual property. Juridical-normative method with statute and conceptual approaches are all applied. The result shows that bezitter is seen as the owner, and thus, a sales-and-purchase transaction as well as the object delivery of virtual property is considered valid and enforceable if it is in accordance to what it has been agreed in End User License Agreement (EULA).